2019
DOI: 10.1039/c8sm02005a
|View full text |Cite
|
Sign up to set email alerts
|

Edge transport at the boundary between topologically equivalent lattices

Abstract: Edge currents of paramagnetic colloidal particles propagate at the edge between two topologically equivalent magnetic lattices of different lattice constant when the system is driven with periodic modulation loops of an external magnetic field. The number of topologically protected particle edge transport modes is not determined by a bulk-boundary correspondence. Instead, we find a rich variety of edge transport modes that depend on the symmetry of both the edge and the modulation loop. The edge transport can … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…A recent study showed directed motion for particles interacting with a periodic lattice substrate in what are called colloidal topological insulators [41,43]. Here, a colloid driven in a circular or closed orbit can exhibit directed transport when interacting with the interface between two different types of substrate lattices.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed directed motion for particles interacting with a periodic lattice substrate in what are called colloidal topological insulators [41,43]. Here, a colloid driven in a circular or closed orbit can exhibit directed transport when interacting with the interface between two different types of substrate lattices.…”
Section: Discussionmentioning
confidence: 99%
“…For colloids interacting with periodic 1D surfaces, various effects such as transitions among liquid, 2D hexagonal solid, and smectic states appear as a function of increasing substrate strength (Bechinger et al, 2001;Tierno, 2012;Tierno et al, 2008). The next level of complexity is to consider colloids interacting with two dimensional periodic arrays, such as an egg carton (Agra et al, 2004;Bohlein et al, 2012;Mangold et al, 2003;Reichhardt and Olson, 2002;Šarlah et al, 2005), muffin tin (Bechinger et al, 2001), or more complex potentials (Demirrs et al, 2013;Gunnarsson et al, 2005;de las Heras et al, 2016;Loehr et al, 2016a;Massana-Cid et al, 2019;Tierno and Fischer, 2014;Yellen et al, 2005). Such systems can mimic the ordering of atoms on 2D surfaces (Coppersmith et al, 1982), vortices in type-II superconductors with nanostructured pinning (Baert et al, 1995;Harada et al, 1996;Martín et al, 1999), and vortices in Bose-Einstein condensates (Tung et al, 2006) interacting with 2D optical trap arrays.…”
Section: Colloids As a Model Systemmentioning
confidence: 99%
“…We have also extensively studied (with computer simulations and experimentally) the topologically protected transport of paramagnetic colloids above single periodic magnetic patterns [16][17][18][19][20]. There, the transport is driven by a uniform external magnetic field of varying orientation.…”
Section: Introductionmentioning
confidence: 99%